New functions of a known autophagy regulator: VCP and autophagy initiation - Lei, Yuchen (Autophagy, 2021)
VCP, a conserved ATPase, is involved in several cellular processes, and mutations in this protein are associated with various diseases. VCP also plays a role in autophagosome maturation. However, because a deficiency in autophagosome maturation presents a readily observable phenotype, other roles of VCP in autophagy regulation, in particular in the initial steps of autophagosome formation, may have been overlooked. In a recently published paper, using small-molecule inhibitors, Hill et al. showed that VCP regulates autophagy initiation through both stabilization of BECN1 and enhancement of phosphati-dylinositol 3-kinase (PtdIns3K) complex assembly.